Problem solving and making team decisions – methods and tools - Mikosik, Piotr (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The aim of the chapter is to present the methodology of team problem solving. Effective decision begins with identifying the nature of the problem. Simple, repetitive problems require routine solutions can be taken individually by the manager. Meanwhile, complex, atypical problems are more effectively solved with the participation of a team using a professional decision-making methodology. What is more, the methodology is necessary if there is a conflict among team members because none of them is willing to compromise, listen to the arguments of others and want to build an agreement. The simplicity of the process and the methods in solving problems are the basis for the team’s effectiveness. For this reason, the author recommends a decision making model consisting of the following stages: problem identification, diagnosis of the situation, search for solutions, evaluation of solutions, implementation. The chapter also presents selected methods used in particular stages of the decision-making process.